Analysis of the Effect of Government Expenditure in the General Services Sector, Infrastructure Sector, and Domestic Investment on Economic Growth in Bali Province - Ni Putu Ayu Wianda Radita Sari; I Made Endra Kartika Yudha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study is motivated by the crucial role of government spending and domestic investment (PMDN) in driving economic growth, particularly in Bali Province, which is heavily reliant on the tourism sector and vulnerable to external shocks such as the COVID-19 pandemic. The objective of this research is to analyze the influence of government expenditure in the general services and infrastructure sectors, as well as domestic investment, on Bali’s economic growth during the 2014–2023 period, both simultaneously and partially. This study employs panel data combining cross-sectional and time-series data from 9 regencies/cities in Bali Province over a 10-year period (2014–2023), using a Random Effect Model (REM) approach after conducting the Chow test, Hausman test, and Lagrange Multiplier test. The results show that, simultaneously, all independent variables significantly influence economic growth. Partially, government spending in general services, infrastructure, health, and education sectors has a positive and significant effect. Meanwhile, expenditure in economic services, domestic investment (PMDN), and the COVID-19 variable have a positive but statistically insignificant effect on economic growth in Bali Province. It is recommended that local governments improve the effectiveness of economic sector spending, promote equitable distribution of domestic investment, and accelerate economic diversification to reduce dependency on tourism and strengthen regional economic resilience.